Use of digital instruments and services in the system of children’s additional education - Yuri Pavlovich Vetrov; Andrey Anatolevich Bezrukov; Lyubov Alekseevna Gorovenko; Stepan Olegovich Krupko (Revista on line de Política e Gestão Educacional)
The study examines digital instruments and services that can be used in the system of additional education. Being able to use digital instruments and services in professional activity and being ready to account for modern trends in the development of digital technology is important for a teacher in additional education. The organizational foundation of additional education is a digital learning platform. Digital technologies require new approaches to the development of educational and methodological materials, types of activities, methods, means, and organizational forms of learning to ensure the high quality of the educational process. The authors explore the use of Google digital services, resources for creating infographics, and MindMeister, a service for creating mind maps, in the system of additional education.